2007
DOI: 10.1063/1.2740190
|View full text |Cite
|
Sign up to set email alerts
|

Polarity control of ZnO films on (0001) Al2O3 by Cr-compound intermediate layers

Abstract: This letter presents a reliable and very easy method for selective growth of polarity controlled ZnO films on (0001) Al2O3 substrates by plasma-assisted molecular-beam epitaxy. Cr-compound intermediate layers are used to control the crystal polarity of ZnO films on (0001) Al2O3. ZnO films grown on rocksalt structure CrN/(0001) Al2O3 shows Zn polarity, while those grown on rhombohedral Cr2O3∕(0001) Al2O3 shows O polarity. Possible interface atomic arrangements for both heterostructures are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 23 publications
3
28
1
Order By: Relevance
“…In this paper, we report the realization of a vertically aligned 1D ZnO nanowires on PPI ZnO heterostructures, which were fabricated using previously proposed in situ polarity control methods [21]. This approach will open the possibility of creating patterned mutidimensional nanostructures for applications as optoelectronics, sensors, and nonlinear optical devices.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this paper, we report the realization of a vertically aligned 1D ZnO nanowires on PPI ZnO heterostructures, which were fabricated using previously proposed in situ polarity control methods [21]. This approach will open the possibility of creating patterned mutidimensional nanostructures for applications as optoelectronics, sensors, and nonlinear optical devices.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the differences of material properties depending on the polarity, various methods are suggested to control the polarity of ZnO films on c-sapphire substrates [19][20][21]. Until now, the polarity control itself has been extensively studied, but the spatial array and applications are not so many reported [22].…”
Section: Introductionmentioning
confidence: 98%
“…ZnO films were grown at 700°C with a Zn beam flux of 0.14 nm/s, while the oxygen flow rate was 1 sccm with an radiofrequency (RF) power of 300 W. Details of the pretreatment and growth of the CrN layer are described elsewhere. 11 The crystal structure and phase of each layer were investigated by high-resolution transmission electron microscopy (HRTEM) and diffraction pattern analysis. A Jeol JEM 3010 TEM operating at 300 keV was used for HRTEM.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 The authors previously reported that polarity control of ZnO was achieved by using Cr compound intermediate layers. 11 In that report, it was demonstrated that CrN could be applied not only for the growth of ZnO with high crystallinity, but also to provide a method for twodimensional polarity control of ZnO films.…”
Section: Introductionmentioning
confidence: 97%
“…Details of CrN layer growth procedures are depicted in Ref. [10]. The HT GaN layer was grown on CrN buffer layers at 800 °C.…”
Section: ×10mentioning
confidence: 99%